2006
DOI: 10.1097/00129689-200604000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Intraperitoneal CO2 Insufflation and Abdominal Wall Lift on QT Dispersion and Rate-corrected QT Dispersion During Laparoscopic Cholecystectomy

Abstract: This study compared the effect of intraperitoneal CO2 insufflation with abdominal wall lift on RR interval, QT interval, the rate-corrected QT (QTc) interval, QT dispersion (QTD), and the rate-corrected QTD (QTcD) using computerized measurement during laparoscopic cholecystectomy. Thirty patients scheduled for laparoscopic cholecystectomy were randomly assigned to 2 groups: intraperitoneal CO2 insufflation (CO2 group) or abdominal wall lift (lift group). A 12-lead electrocardiogram was monitored to measure par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…[ 47 ] CO 2 pneumoperitoneum also predisposes the patient to cardiac arrhythmias. [ 49 ] During the early phase of pneumoperitoneum, there is a reduction in the cardiac output[ 46 47 ] by decreasing the venous return. [ 50 ] Although these cardiorespiratory changes may be tolerated by healthy adults with adequate cardiopulmonary reserve, people with cardiopulmonary disease may not be able to tolerate these cardiopulmonary changes.…”
Section: Discussionmentioning
confidence: 99%
“…[ 47 ] CO 2 pneumoperitoneum also predisposes the patient to cardiac arrhythmias. [ 49 ] During the early phase of pneumoperitoneum, there is a reduction in the cardiac output[ 46 47 ] by decreasing the venous return. [ 50 ] Although these cardiorespiratory changes may be tolerated by healthy adults with adequate cardiopulmonary reserve, people with cardiopulmonary disease may not be able to tolerate these cardiopulmonary changes.…”
Section: Discussionmentioning
confidence: 99%
“…51 CO 2 pneumoperitoneum also predisposes to cardiac arrhythmias. 53 During the early phase of pneumoperitoneum, there is a reduction in the cardiac output 50,51 by decreasing the venous return. 54 Although these cardiorespiratory changes maybe tolerated by healthy adults with adequate cardiopulmonary reserve, people with cardiopulmonary diseases may not tolerate these cardiopulmonary changes.…”
Section: Discussionmentioning
confidence: 99%
“…A number of small prospective trials have demonstrated that although such an approach causes fewer cardiopulmonary disturbances than pneumoperitoneum, operative times and postoperative pain are increased, with no appreciable differences in morbidity or mortality. 710 Although abdominal lift procedures may have a role in very specific patient populations, our results suggest that traditional pneumoperitoneum can be tolerated safely in most patients with CHF.…”
Section: Discussionmentioning
confidence: 80%